Kilka uwag na temat komunikacji interpersonalnej w Ajschylosowym Agamemnonie - Wesołowska, Elżbieta (Przestrzenie Teorii, 2019)
The presented paper considers the problem of misunderstanding between two people on the ancient stage. The author chose two dramatical interrelations in Agamemnon by Aeschylus. Each of these dialogues presents different incongruity between question or order and the response, which can be caused from one side in the pride, power, and fear, and suffering or weakness from the other. We should undertake also some details concerning the importance of silence during the dramatic conversation, sometimes neglected by the scholars. The participant (reader or spectator) of such passages may feel uncertain, if this is a sophisticated play of the author with him, or even a vestige of his interest in human psychology.